Calcium fructoborate regulate colon cancer (Caco‐2) cytotoxicity through modulation of apoptosis. Issue 5 (17th February 2022) - Kisacam, Mehmet A.; Ambarcioglu, Pinar; Yakan, Akin
Abstract: Sugar‐borate esters have recently been reported to have anti‐cancer potential. Among the sugar‐borate esters, calcium fructoborate (CaFB) possesses beneficial effects on human health. Despite the beneficial effects of CaFB, there is a lack of knowledge about their mode of action in cancer. The potential cytotoxic effects of CaFB were investigated on colon cancer cells (Caco‐2). The mode of action was determined through the evaluation of Fyn and Hck expression levels together with Bcl‐2, Bax, and PI3K/Akt pathway proteins. CaFB treatment was found to be most effective on Caco‐2 cells at 10 mM concentration for 24 h. Decreased Bcl‐2 levels and increased Bax levels at 10 mM were evaluated as an indicator of apoptotic effects of CaFB. Akt, p70S6K, and 4EBP1 levels, in general, tend to decrease following CaFB, while PTEN and TSC2 levels have been found to increase. Furthermore, CaFB upregulated Hck expression and downregulated Fyn expression. In conclusion, our results indicated that CaFB treatment at 10 mM concentration, the IC50 dose found in our study, might prevent colon cancer cell proliferation both by inducing apoptosis and presumably by activating autophagy.